From fuzzy transportation problem to non-linear intuitionistic fuzzy multi-objective transportation problem: A literature review. (3rd September 2021) - Chhibber, Divya; Srivastava, Pankaj Kumar; Bisht, Dinesh C.S.
ABSTRACT: To deal with the unpredictability of certain parameters of the transportation problem like fuel charges, climatic conditions, supply and demand of the product, etc., the concept of fuzzy transportation problem came into the limelight. It has been proved to be an efficient approach and extended in literature by various scholars. In the given paper, the existing methods to obtain the solution of different types of fuzzy transportation problem and its extensions are critically reviewed. Intuitionistic fuzzy transportation problems having single and multiple objectives have been focused upon. A review of the past ten years has been done to know the recent advancement. Tabular and graphical comparisons of different approaches are incorporated to understand their benefits and drawbacks.